PENGARUH KOMUNIKASI DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA ORGANISASI DI POLITEKNIK PIKSI GANESHA BANDUNG - Bambang Ermansyah Saragih (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
Effective communication occurs when individuals reach mutual understanding, stimulate others to take action, and encourage people to think in new ways. The ability to communicate effectively will increase productivity, both the individuals concerned and their organizations, so that they can anticipate problems, make decisions effectively, coordinate workflow, supervise others, develop relationships and can promote organizational products and services. This study aims to identify the influence of communication and the quality of human resources on organizational performance in Piksi Ganesha Bandung Polytechnic. From the results of the above research, the authors provide the following suggestions: 1) the need for an integrated communication system so that all human resources in the organization can find out information related to their tasks quickly and accurately; 2) periodic training needs to be held so that it can improve organizational performance and improve self-understanding among employees; 3) development of communication systems between employees and between campus locations so as to minimize errors or confusion of information in the organization.